Conservation of Damar Mata Kucing (Shorea javanica): A Review on the Aspect of Trade System - Hanifah Nur'aini; Ervizal A. M. Zuhud; Tutut Sunarminto (Jurnal Manajemen Hutan Tropika, 2020)
Damar mata kucing (Shorea javanica) is one of the non-timber forest products (NTFP)s that has been widely managed and utilized by local people around the Pesisir Barat Lampung Province. The majority of repong damar has been cut down, especially during the last 15 years. One of the reasons for decreasing community interest in managing repong dammar is the decreasing of dammar gum prices. This research aimed to analyze the market system of dammar cultivation in Pesisir Barat, Lampung Province. Descriptive analysis was used to determine the local community's knowledge, skill, and opinion in the trading channel. For further analysis, marketing margin and farmers' share were also used to analyze the price differentiation from the producer's level to the consumer's level. Based on the study results, there are three channels of the dammar gum market in Pesisir Barat Lampung. Most of the farmers (up to 85.71% of total) in Pekon Pahmungan use trading channels 1 and 2 to sell their harvested dammar. Meanwhile, based on the analysis of profit margin, it appears that farmers in channels 1 and 2 are trading actors that receive the lowest profit margin (IDR7,100 kg-1 and IDR8,100 kg-1) compared to trading channel 3 (IDR14,000 kg-1). Farmer's share obtained by dammar farmers in this study was 55.30% on channel 1, 52.20% on channel 2, and 76.80% on channel 3. Livelihood, limitation on capital, lack of information and networking, knowledge and abilities to tree management and harvested dammar, knowledge of another use of dammar gum, and the ability to use technology directly affecting farmers' position in the dammar gum trading system.